TANTANGAN DAN STRATEGI PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH MELALUI PUSAT LAYANAN USAHA TERPADU - Adhi Prasetyo Satriyo Wibowo (Pusat Kajian Anggaran, 2023)
The MSME Integrated Management Major Project was launched by the government to integrate various policies across sectors and regions under the supervision of the Ministry of Cooperatives. Since 2014, there has been an Integrated Business Service Center (PLUT). This article aims to analyze the challenges and strategies for empowering MSMEs through PLUT using a qualitative descriptive approach. Empowering MSMEs faces fundamental problems such as a single database, financing, licensing, partnerships, and mentoring for MSMEs. This problem has not been able to be resolved by PLUT or through various MSME empowerment programs carried out by the government spread across ministries and institutions at this time. So that the empowerment of MSMEs through the Integrated Business Service Center can be more optimal, it is necessary to strengthen the institutional structure of the Integrated Business Service Center, which is carried out through government regulations.